New Trends in Performing Arts in Korea: The Convergence of Pansori and Korean Contemporary Dance - Yesol Seo; Hwihyun You; Austin Kang (SAGE Open, 2023)
Pansori, traditional Korean music, has recently been expanding its boundaries and increasing its sustainability through collaboration with other genres. The present study aimed to evaluate panelists’ perceptions of new trends in performing arts in Korea, focusing on the convergence of Pansori and Korean contemporary dance. This study analyzed panelists’ perceptions of the convergence of Pansori and Korean contemporary dance using the Delphi technique. Thus, 20 panelists on Pansori and Korean contemporary dance were recruited to propose a facilitation strategy for converging the two performing arts. This study was conducted over 3 months, from November 2021 to January 2022. A total of three Delphi rounds were held, and the panel reached a consensus in five areas. The panel suggested various facilitation strategies: development of performing arts content for convergence of Pansori and Korean contemporary dance; reinforcing manpower exchanges between Pansori and Korean contemporary dance; improving the treatment of performers; reasonable ticket prices; and reinforcing government support policies. As a result, this study shows that the fusion performance of traditional and contemporary elements, Pansori and Korean contemporary dance, needs to explore blending disciplines and styles, breaking traditional boundaries, and exploring new creative expressions.